Analysis of the Acceptance of Use of SIPP Information System at Pengadilan Agama Penajam - Haliandari Haliandari; Elvin Leander Hadisaputro; Nuorma Wahyuni (STMIK PONTIANAK, 2022)
The purpose of this study was to determine the level of acceptance of the use of the SIPP Application using the Technology Acceptance Model (TAM) Method on the Information System at the Pengadilan Agama Penajam. This research is research with the type of data used consists of primary data and secondary data. The research population includes all employees at the Pengadilan Agama Penajam who use the SIPP information system, by distributing questionnaires to all employees using the SIPP information system at the Pengadilan Agama Penajam as many as 25 employees. The results showed that the actual level of acceptance of the use of AU has a positive and significant effect on the use of the SIPP information system, which means that the SIPP information system has provided benefits to users. Similarly, the results of the analysis using the Perceived usefulness (PU) variable with a Sig value of 0.368 > 0.05 and a T value of -0.921 < 2.085. Perceived ease of use (PEOU) with a Sig value of 0.718 > 0.05 and a T count of 0.366 < 2.085. Attitude Toward Usage (ATU) with a Sig value of 0.007 < 0.05 and a T count of 3.020 > 2.085. Behavioral Intention (BI) Behavioral Intention has a positive and significant effect on users of the SIPP information system at the Pengadilan Agama Penajam with a Sig value of 0.004 < 0.05 and a T count of 3.202 > 2.085. Actual System Use (AU) the actual use of the system in the level of acceptance of the use of the SIPP information system